ANALISIS KONSEP PENTAHELIX DALAM PENGEMBANGAN EDU WISATA SEBAGAI UPAYA MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA HENDROSARI KECAMATAN MENGANTI KABUPATEN GRESIK - Asy’ari, Maulana Nur Hasyim; Astuti, Sri Juni Woro (MAP (Jurnal Manajemen dan Administrasi Publik), 2025)
This research explains the results of the analysis of the application of the pentahelix collaboration concept in an effort to develop educational tourism destinations in Hendrosari Village and the impact after the activities of Stakeholders in the development of the welfare conditions of the Hendrosari Village community. The approach used in this research uses descriptive qualitative method. The pentahelix actors involved in the collaborative development process have carried out their roles and functions optimally, but for actors private has not been involved in the collaboration process. In the aspect of development benchmarks, it is known that the focus of educational tourism development is concentrated on ecological-based empowerment and local community empowerment and economic development, so that for the dimensions of social and cultural development there has been no effort made by pentahelix stakeholders. The condition of the welfare of the people of Hendrosari Village after the development and construction of the Lontar Sewu Educational Tourism carried out by the pentahelix actor could not be categorized as ideally prosperous, this is because in the observations of the researchers found inequality in the provision of wages or salaries of employees which incidentally the Hendrosari village community are different and not proportionally and the lack of allocation of the original income of Hendrosari Village which is used for village community empowerment programs.